Quality of Service (QoS) Jaringan Wireless Local Area Network (WLAN) Pada Universitas Papua : (Quality of Service (QoS) Wireless Local Area Network (WLAN) in Papua University) - Elisabet Damanik; Christian Dwi Suhendra; Lion. F. Marini (Universitas Papua, 2022)
Almost every building area at the University of Papua has been facilitated with a Wireless Local Area Network (WLAN). Each user has one account to use the facility. But as more users access the network simultaneously allowing the occurrence of a slowed network connection and become less stable. Network monitoring and analysis is carried out to determine the quality of the network in each area of the building. Axence NetTools 5 is one of the applications that easy-to-use monitoring carried out in 3 building areas, Unit Pelayanan Teknis Komputer (UPT-TIK), Rektorat dan Fakultas Sastra dan Budaya. To measure the Quality of Service (QoS) of the network with parameters bandwidth, throughput, delay, jitter, and packet loss using TIPHON standardization. The results from the three access points areas belong to the category of “Satisfactory”. For all the quality of the WLAN internet network at the University of Papua in the three building areas is